Field evaluation of a 0.005% fipronil bait, orally administered to Rhombomys opimus, for control of fleas (Siphonaptera: Pulicidae) and phlebotomine sand flies (Diptera: Psychodidae) in the Central Asian Republic of Kazakhstan. - David M Poché; Zaria Torres-Poché; Aidyn Yeszhanov; Richard M Poché; Alexander Belyaev; Vit Dvořák; Zaure Sayakova; Larisa Polyakova; Batirbek Aimakhanov (Public Library of Science (PLoS), 2018)
Plague (Yersinia pestis) and zoonotic cutaneous leishmaniasis (Leishmania major) are two rodent-associated diseases which are vectored by fleas and phlebotomine sand flies, respectively. In Central Asia, the great gerbil (Rhombomys opimus) serves as the primary reservoir for both diseases in most natural foci. The systemic insecticide fipronil has been previously shown to be highly effective in controlling fleas and sand flies. However, the impact of a fipronil-based rodent bait, on flea and sand fly abundance, has never been reported in Central Asia. A field trial was conducted in southeastern Kazakhstan to evaluate the efficacy of a 0.005% fipronil bait, applied to gerbil burrows for oral uptake, in reducing Xenopsylla spp. flea and Phlebotomus spp. sand fly abundance. All active gerbil burrows within the treated area were presented with ~120 g of 0.005% fipronil grain bait twice during late spring/early summer (June 16, June 21). In total, 120 occupied and 14 visited gerbil colonies were surveyed and treated, and the resulting application rate was minimal (~0.006 mg fipronil/m2). The bait resulted in 100% reduction in Xenopsylla spp. flea abundance at 80-days post-treatment. Gravid sand flies were reduced ~72% and 100% during treatment and at week-3 post-treatment, respectively. However, noticeable sand fly reduction did not occur after week-3 and results suggest environmental factors also influenced abundance significantly. In conclusion, fipronil bait, applied in southeastern Kazakhstan, has the potential to reduce or potentially eliminate Xenopsylla spp. fleas if applied at least every 80-days, but may need to be applied at higher frequency to significantly reduce the oviposition rate of Phlebotomus spp. sand flies. Fipronil-based bait may provide a means of controlling blood-feeding vectors, subsequently reducing disease risk, in Central Asia and other affected regions globally.